Tandem-ring mill pulverization benefits for enzymatic saccharification of biomass - Takahashi, Takehiko; Ito, Kazushi; Ito, Arata; Enda, Yukio; Gochi, Motohiro; Mori, Hideaki; Kobayashi, Junichi (Renewable energy, 2014)
A vibration mill, called a "tandem-ring mill", which has cog-ring media in place of the ball medium of a conventional vibration mill, was developed to achieve high-impact pulverization of lignocellulosic biomass for bio-ethanol production. This study investigated pulverization characteristics of various biomass samples of Japanese cedar, eucalyptus, rice straw, rice husk, and reeds using a batch-type tandem-ring mill for 60 min and 100 min pulverizations. The pulverized biomasses were characterized by the mean particle diameter, crystallinity index, and enzymatic saccharification. The mean particle diameter of biomass was decreased rapidly in the first 20 min. Then the biomass mean particle diameter reached around 40 mu m by flocculation. Furthermore, the crystallinity indexes of biomasses were decreased by pulverization. Especially, woody biomasses of cedar and eucalyptus were decreased rapidly around 10%, nearly a non-crystalline state. Woody biomasses, Japanese cedar, and eucalyptus showed high saccharification efficiency. Similarly, grass biomasses, rice straw, and rice husks showed high saccharification, aside from reeds. Therefore pretreatment of various biomasses using a tandem-ring mill was suitable for enzymatic saccharification.